2013
DOI: 10.1111/1462-2920.12106
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic detection of novel Cryptomycota in an Iowa (United States) aquifer and from previously collected marine and freshwater targeted high‐throughput sequencing sets

Abstract: Fungi are everywhere and interact with humans in countless ways, but a large group of fungi called 'Cryptomycota' has escaped detection until very recently. Still, the extent of diversity and ecological habits of this group remain largely unknown. We interrogated publically available 18S rRNA gene datasets, obtained via high-throughput sequencing from marine and freshwater samples, for Cryptomycota sequences. Contrary to previous work, we found evidence of substantial Cryptomycota diversity in the marine upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Previous investigation has shown that nucleotide distances between different variable regions of the rRNA gene are tightly correlated (Livermore and Mattes, 2013) which indicates that this is a reasonable approximation. The use of phylogenetic diversity and previously defined reference OTUs dramatically reduces the sensitivity of our results to this potential issue.…”
Section: Neutral Model Of Local-global Overlapmentioning
confidence: 73%
“…Previous investigation has shown that nucleotide distances between different variable regions of the rRNA gene are tightly correlated (Livermore and Mattes, 2013) which indicates that this is a reasonable approximation. The use of phylogenetic diversity and previously defined reference OTUs dramatically reduces the sensitivity of our results to this potential issue.…”
Section: Neutral Model Of Local-global Overlapmentioning
confidence: 73%
“…In particular, high-throughput sequencing (HTS) technologies enable documentation and characterization of hundreds to thousands of species simultaneously from biological samples. These methods have been used successfully to uncover diversity and community composition of fungi in various substrates and localities, including little-studied habitats such as mangroves, aquatic ecosystems, and arctic soils (Arfi et al 2012;Blaalid et al 2013;Livermore and Mattes 2013). Similarly to other amplicon-based methods, HTS techniques are sensitive to PCR and primer biases (Lindahl et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found Cryptomycota are highly diverse in freshwater habitats, yet have identified clades that were dominated by marine or aquifer sequences (Livermore and Mattes, 2013). We found freshwater sediment and soil representatives both widely distributed across the Cryptomycota phylogeny.…”
Section: Resultsmentioning
confidence: 49%
“…These fungi are quite common in aquatic and marine environments where their abundance may range from 0.02 to 30 % of all eukaryotic sequences, with an average of 3.5 % across 13 studies (Livermore and Mattes, 2013). While direct ecosystem effects from parasites of producers are more readily observed, Rozella and similar hyperparasites may have a considerable regulatory role on population sizes of zoosporic fungi that are parasites of primary consumers in lakes (Gleason et al, 2012(Gleason et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation